Promoting Religious-Friendly Tourism for Developing Religious Harmony: A Study of Tourist Gaze - Bahri Soi, Andi; Pahlawan Putra, Adhitia; Kamal Zubair, Muhammad; Markarma Yusup, Andi; Megandani, Adi (Center for Research and Development of Religious Literature and Heritage, 2023)
In the process of Islamization of Nusantara, there was an interaction between Islam and local civilizations in various regions of Nusantara, which then became attractive objects for tourist gaze, including in Bali. Some areas such as Denpasar, Badung and Bangli were not much known as the entrance points of Islam in Bali. Tourist gaze has been concentrated on pleasure and leisure with a focus on popular tourist attractions and hotelaccommodations, as well as cultural authenticities. This article aims to explore the potential of tourism industry by promoting the aspect of interreligiosity (such as between Balinese Hindu and Islam) to reconstruct the religious-friendly tourism of Bali.Â The study employed principles of netnography and literature study. The data was obtained from the internet, books, and journals, as well as a systematic literature review through Publish or Perish (PoP). The data is presented in narrative analysis and interpretations. The results of the study suggest that inter-religiosity could be integrated into the tourism industry. Some religious-friendly tourist destinations can be reconstructed through representations of inter-religious relationships in Denpasar, Badung, and Bangli. As such, religious-friendly tourism could support the development of harmonious life for a sustainable civilization. For further research, it is suggested to conduct research on other tourist gaze areas that are limited by this work.